PLC online - Angon, Rommel M. (1999)
PLC Online is a web based programmable logic controller. It can be accessed using any browser. The advantages of drawing the visual representation of a ladder diagram are it is user friendly and it consumes less time. Instead of keying the values of each element in the ladder logic the same task can be accomplished by just dragging the figures. Implementing it as web based, more users can access the PLC.